Wound formation in patients with Rutherford category IV disease after endovascular therapy: rates and risk factors - Toshihiko Kishida; Shinsuke Mori; Kohei Yamaguchi; Masakazu Tsutsumi; Norihiro Kobayashi; Yoshiaki Ito (CVIR Endovascular)
Abstract Background Lower limb peripheral artery disease classified as Rutherford category IV, is characterized by lower limb ischemic pain both during exertion and at rest. This disease has an unclear course. We aimed to evaluate outcome predictors in this patient group after endovascular therapy. This single-center, retrospective, observational study included 234 consecutive patients (264 limbs), between April 2007 and December 2020. We investigated the disease clinical course after endovascular therapy. The primary endpoint was the wound formation rate 3 years after endovascular therapy. Results The mean observation period was 48.2 ± 8.9 months. The patients (61.9% male; mean age, 76 ± 10 years) presented with diabetes (64.1%), and received hemodialysis with chronic kidney disease (35.0%) and ambulatory treatment (85.0%). The average ankle-brachial index before endovascular therapy was 0.69 ± 0.23. Skin perfusion pressure on the dorsal and plantar sides was 38 ± 13 mmHg and 36 ± 12 mmHg, respectively. The wound incidence rates at 1, 2, and 3 years after endovascular therapy were 8.3%, 11.4%, and 14.4%, respectively. Multivariate analysis revealed the following factors associated with wound formation: P2 in inframalleolar/pedal disease category in the Global Limb Anatomical Staging System (hazard ratio: 1.73, 95% confidence interval: 1.22–2.83, P = 0.01), non-ambulatory status (hazard ratio: 1.09, 95% confidence interval: 1.11–1.36, P = 0.02), intervention up to infrapopliteal lesion (hazard ratio: 1.55, 95% confidence interval: 1.17–2.46, P = 0.03), and patient with chronic kidney disease on hemodialysis (hazard ratio: 1.61, 95% confidence interval: 1.32–2.18, P = 0.03). Conclusions The 3-year incidence of wound onset in this study was 14.4%. Factors associated with this outcome included P2 in the Global Limb Anatomical Staging System, non-ambulatory status, intervention up to infrapopliteal lesion, and patient with chronic kidney disease on hemodialysis.